Bilateral gradient‐echo spectroscopic imaging with correction of frequency variations for measurement of fatty acid composition in mammary adipose tissue. Issue 1 (2nd February 2021) - Baboli, Mehran; Storey, Pippa; Sood, Terlika Pandit; Fogarty, Justin; Moccaldi, Melanie; Lewin, Alana; Moy, Linda; Kim, Sungheon Gene
Abstract : Purpose: To develop a simultaneous dual‐slab three‐dimensional gradient‐echo spectroscopic imaging (GSI) technique with frequency drift compensation for rapid (<6 min) bilateral measurement of fatty acid composition (FAC) in mammary adipose tissue. Methods: A bilateral GSI sequence was developed using a simultaneous dual‐slab excitation followed by 128 monopolar echoes. A short train of navigator echoes without phase or partition encoding was included at the beginning of each pulse repetition time period to correct for frequency variation caused by respiration and heating of the cryostat. Voxel‐wise spectral fitting was applied to measure the areas of the lipid spectral peaks to estimate the number of double‐bond (ndb), number of methylene‐interrupted double‐bond (nmidb), and chain length (cl). The proposed method was tested in an oil phantom and 10 postmenopausal women to assess the influence of the frequency variation on FAC estimation. Results: The frequency drift observed over 5:27 min during the phantom scan was about 10 Hz. Phase correction based on the navigator reduced the median error of ndb, nmidb, and cl from 9.7%, 17.6%, and 3.2% to 2.1%, 9.5%, and 2.8%, respectively. The in vivo data showed a mean ± standard deviation frequency drift of 17.4 ± 2.5 Hz, with ripples at 0.3 ± 0.1 Hz. Our reconstruction algorithm successfully separated signals from the left and right breasts with negligible residual aliasing. Phase correction reduced the interquartile range within each subject's adipose tissue of ndb, nmidb, and cl by 18.4 ± 10.6%, 18.5 ± 13.9%, and 18.4 ± 10.6%, respectively. Conclusion: This study shows the feasibility of obtaining bilateral spectroscopic imaging data in the breast and that incorporation of a frequency navigator improves the estimation of FAC.